BIOKINETICS OF ORGANICS AND NUTRIENTS REMOVAL OF WASTEWATER TREATMENT USING PALM OIL CLINKER (POC) MEDIA IN A SUBMERGED ATTACHED GROWTH SYSTEM - AL-DHAWI, BAKER NASSER SALEH (2021)
An attached-growth system is a biological treatment that utilizes microorganisms that are attached to the fixed media to remove organic matter, nutrients, and other constituents in wastewater